Training organisations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The African Publishers Network (APNET), set up to promote local publishing in Africa, now brings together national publishers associations in more than 27 countries in Africa. It organises short-courses on publishing techniques.PO Box 3773,...